An assessment of the taxation of Income derived from illegal activities in Zimbabwe - Nyathi, Conrad Clinton Melusi (Midlands State University, 2020)
In Zimbabwe, the question as to whether income derived by a taxpayer whilst pursuing illegal activities should be made subject to the Income Tax Act of Zimbabwe (hereinafter the Act), is a relatively uncharted area of the law. Compared to other jurisdictions like South Africa and the United States of America (hereinafter USA), which have been developing this area of the law through case law and scholarly writings, the subject has been dormant in Zimbabwe. This research will draw comparisons between the taxation regime relating to the taxation of income derived from illegal activities as it stands in Zimbabwe and that of South Africa and the USA. One is only taxed in terms of the gross income they have ‘received’ in any year of assessment, hence the problem arises, does one ‘receive’ income derived from illegal activities? In Zimbabwe, the prominent decision on whether or not income derived from illegal activities is to be taxed is Commissioner of Taxes v G (hereinafter COT v G). The crux of the Courts finding in this case was that, this form of income is not ‘received’ for purposes of the Act. The court pursued the objective approach to the taxation of income derived from illegal activities. The objective approach is when a court applies the literal rule of interpretation to the word ‘receive’. According to this approach a taxpayer ‘receives’ an amount if they have legal entitlement over it. Legal entitlement over an amount is absent if, upon such seeming receipt, a legal obligation to pay the amount over to another person immediately arises.